Solidification microstructure and residual stress correlations in direct energy deposited type 316L stainless steel. (September 2021) - Guo, Da; Yan, Kun; Callaghan, Mark D.; Daisenberger, Dominik; Chatterton, Mark; Chen, Jiadong; Wisbey, Andrew; Mirihanage, Wajira
Graphical abstract: Highlights: Residual stress and microstructure of an additively manufactured plate was studied. Significant mesoscopic variations in the residual stresses were revealed. The mesoscopic residual strain and microstructures are reckoned together. Abstract: Localised fluctuation in residual stress distribution for direct energy deposited 316L stainless steel thin plate was revealed through high-energy synchrotron X-ray diffraction. The macroscopic residual stress levels are changed steadily across the article according to the characteristic cooling rates, as implied by the measured dendrite arm lengths. Localised fluctuations of residual stress in the length scale, between 500 and 600 µm, coincides well with the morphological variations of the solidification microstructure that formed during direct energy deposition. Computations indicate a greater propensity for related mesoscopic thermal gradient fluctuations along the solidification front of the moving melt pool. Novel perspectives on residual stress across multiple length-scales and its relevance to the formation of solidification microstructure in metal additive manufacturing is analysed by considering the experimental results.